Gas adsorption capacity changes in coals of different ranks after liquid nitrogen freezing. (15th May 2021) - Qin, Lei; Wang, Ping; Li, Shugang; Lin, Haifei; Wang, Ruizhe; Wang, Pei; Ma, Chao
Graphical abstract: Highlights: The effect of liquid nitrogen is related to coal rank. Different functional groups have different changing laws. The contact angle of coal affects the gas adsorption capacity. Abstract: Fracturing coal with liquid nitrogen (LN2 ) has a positive effect on coalbed methane (CBM) extraction. The purpose of this study is to investigate the gas adsorption capacity of coals of different ranks after the coals are frozen with LN2 . For this purpose, gas adsorption tests, contact angle measurements, and Fourier transform infrared spectroscopic analyses were conducted on both non-frozen samples of lignite, bituminous coal, and anthracite and on identical samples after the samples had been frozen by immersion in LN2 . The test results show that after LN2 freezing for 180 min, the maximum amounts of gas that can be adsorbed by the three types of coal are reduced, the coals' contact angles are smaller, and the proportions of several surface functional groups on the coals change. The effects of LN2 freezing on the coals are related to the coal's rank. With the increase of coal rank, the influence on the gas adsorbed capacity of coal first increases and then decreases. The gas adsorption capacities of the coals are linearly correlated with proportions of aliphatic hydrocarbon, oxygen-containing, and substituted benzene functional groups but in a quadratic polynomial relationship with the contact angle. The results of the research reported here clarify the gas adsorption characteristics for coals of different ranks frozen by LN2 and advance our understanding of LN2 fracturing technology.